The Moderating Role of Data Privacy and Protection Security on Service Quality, Brand Equity, and Tariff Towards Firm Performance - Radito Maulana Putra; Mira Maulida; Moch Riyadh Rizki (Conference Series, 2020)
Indonesia had more than 200 million cyber-attacks. Due to its poor cybersecurity system, the country is subject to frequent attacks. As an illustration, in one week in January Indonesia experienced 1.35 million website attacks. The most recent major cyber-attacks in Indonesia happened during the ‘WannaCry’ ransomware attack in May 2017. 12 institutions in Indonesia were attacked, including plantation and manufacturing companies as well as universities. With 355 million telecom subscribers in total as of June 2019 (fourth-largest cellular market in the world) Indonesia still has extremely low awareness of the essentials of data privacy and protection security while few of the major telecom operators that offer prime data privacy and protection are a major distinguishing factor of service quality excellence. The Journal will have as main objective the evaluation of the Data Privacy and Security Protection of mobile telecommunications perceived by the clients towards its brand Equity and firm performance. The relationship and impact between data privacy and protection security as a moderating role with other 5 dependent variables were tested in different periods of telecom professionals and enthusiasts from different regions. This study applied quantitative analysis with data received from 215 high level telecom professionals from major operators and vendors who had extensive experience and knowledge within the Telecom Industry.